A 370 nm ultraviolet cut-off cover plate glass for perovskite solar cell packaging and a preparation method thereof

CN123003142APending Publication Date: 2026-10-30CNBM RESEARCH INSTITUTE FOR ADVANCED GLASS MATERIALS GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610968636.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]本发明的目的是为了解决钙钛矿太阳能电池中钙钛矿活性层材料因紫外线持续照射,引起晶体结构降解与老化,导致电池的光电转换效率快速衰减,以及紫外截止镀膜玻璃无法进行钢化加工等问题,本发明提供了一种钙钛矿太阳能电池封装用370nm紫外截止盖板玻璃及其制备方法

Benefits of technology

通过在玻璃基体(钠钙硅酸盐玻璃、硼硅酸盐玻璃或铝硅酸盐玻璃)中直接加入紫外截止功能剂,可直接制得具有紫外截止功能的盖板玻璃(370nm处透过率小于3.5%,400nm~800nm平均透过率大于84.5%,300nm~380nm平均透过率小于1.2%),屏蔽效果优异并且具有优异的可见光透过率;且本发明制备的盖板玻璃可再次进行强化处理(化学钢化或者物理钢化处理);适合用作钙钛矿太阳能电池用盖板玻璃。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application relates to a 370nm ultraviolet cutoff cover plate glass for perovskite solar cell packaging and a preparation method thereof, characterized in that (1) a sodium calcium silicate glass, a borosilicate glass or an aluminum silicate glass base component and an ultraviolet cutoff functional agent component are weighed, and the ultraviolet cutoff functional agent component is composed of CeO2: 1%-3%, TiO2: 1%-3%, Fe2O3: 0-2%, ZnO: 0.1%-1%, V2O5: 0-1% and Sm2O3: 0-1%; (2) the raw materials are dried; (3) after pretreatment through screening, precise batching and mixing are carried out, the mixed material is placed in a platinum-rhodium alloy crucible, high-temperature melting and pouring forming are carried out through a high-temperature furnace, and slow annealing is carried out. The application has the following advantages: the prepared ultraviolet cutoff cover plate glass has a transmittance of less than 3.5% at 370nm, an average transmittance of greater than 84.5% at 400nm-800nm, and an average transmittance of less than 1.2% at 300nm-380nm; the prepared cover plate glass can be subjected to strengthening treatment again; and the cover plate glass is suitable for being used as a cover plate glass for perovskite solar cells.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of special functional glass manufacturing and photovoltaic packaging technology, specifically relating to a 370nm ultraviolet cutoff cover glass for perovskite solar cell packaging and its preparation method. Background Technology

[0002] Perovskite solar cells have become a key research and industrialization direction for next-generation photovoltaic cells due to their advantages such as high photoelectric conversion efficiency, simple fabrication process, and low cost. However, the perovskite active layer is extremely sensitive to near-ultraviolet light. Long-term exposure to ultraviolet light can easily lead to aging and failure problems such as crystal structure collapse and component decomposition, significantly shortening the service life of the cell module. Therefore, using ultraviolet-blocking cover glass for encapsulation and protection is the key to ensuring the stable operation of perovskite cells.

[0003] Currently, most mainstream UV-protective cover glass on the market uses surface coating modification, achieving UV shielding by depositing organic or inorganic UV-blocking films. However, this type of coated glass has inherent defects: it cannot be tempered at high temperatures after coating, while tempering before coating involves complex processes, glass is prone to spontaneous breakage, yield is low, and production costs are high, making it difficult to meet the needs of large-scale mass production.

[0004] To address the drawbacks of coated glass, the industry has gradually developed bulk-modified 380nm UV-cutoff photovoltaic glass, which can achieve wide-band UV light blocking and a higher level of protection. However, this type of 380nm cutoff glass has significant application limitations. To achieve complete cutoff in the 380nm band, a high doping content of UV-modifying components is required, which not only significantly increases raw material and manufacturing costs, resulting in severe product premiums, but also easily causes light absorption loss in the visible light band due to excessive modifying components, leading to low overall visible light transmittance of the glass, which directly affects the photoelectric conversion efficiency of perovskite solar cells.

[0005] In practical industrial applications, most general-purpose, conventionally used perovskite solar cells do not require the ultra-high protection performance of 380nm full-band ultraviolet shielding. Efficient blocking of the core harmful near-ultraviolet band (300nm-380nm) is sufficient to meet long-term stable operation requirements. 380nm ultraviolet cut-off glass exhibits significant performance redundancy and cost waste, and its insufficient light transmittance fails to meet the industrialization demands of both low cost and high power generation efficiency. Based on the differentiated layout concept of a series of ultraviolet cut-off glasses, this paper proposes developing a low-cost, high visible light transmittance 370nm ultraviolet cut-off cover glass precisely adapted to general packaging scenarios. This fills a gap in the niche market, improves the photovoltaic packaging glass product system, and has significant practical application value. Summary of the Invention

[0006] The purpose of this invention is to solve the problems of perovskite active layer material degradation and aging caused by continuous ultraviolet radiation, resulting in rapid decline of photoelectric conversion efficiency of the cell, and the inability to temper ultraviolet cut-off coated glass. This invention provides a 370nm ultraviolet cut-off cover glass for perovskite solar cell encapsulation and its preparation method.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A 370nm UV cutoff cover glass for encapsulating perovskite solar cells, comprising a glass substrate (sodium-calcium silicate glass, borosilicate glass, or aluminosilicate glass), characterized in that: a UV cutoff functional agent is added to the glass substrate, wherein the UV cutoff functional agent, expressed as a mass percentage based on oxides, comprises the following proportions in the glass substrate: CeO2: 1%~3%, TiO2: 1%~3%, Fe2O3: 0~2%, ZnO: 0.1%~1%, V2O5: 0~1%, Sm2O3: 0~1%.

[0008] Furthermore, the ultraviolet blocking functional agent, expressed as a mass percentage based on oxides, has the following proportions in the glass matrix: CeO2: 1.2%-2.0%, TiO2: 1.2%-2.0%, Fe2O3: 0-1.0%, ZnO: 0.2%-0.5%, V2O5: 0-0.5%, Sm2O3: 0-0.5%.

[0009] Furthermore, the sodium-calcium silicate glass, expressed as a mass percentage based on oxides, is composed of the following substances: SiO2: 65-75%, Na2O: 10-25%, CaO: 5-15%, MgO: 1-5%, Al2O3: 0-3%.

[0010] Furthermore, the borosilicate glass, expressed as a mass percentage based on oxides, is composed of the following substances: SiO2: 75~83%, Na2O: 1~5%, B2O3: 6~15%, CaO: 0.5~2%, Al2O3: 0~3%.

[0011] Furthermore, the aluminosilicate glass, expressed as a mass percentage based on oxides, is composed of the following substances: SiO2: 60~69%, Na2O: 5~9%, Li2O: 2~5%, K2O: 1~5%, MgO: 3~9%, Al2O3: 16~24%.

[0012] Furthermore, the 370nm UV cutoff cover glass for perovskite solar cell encapsulation has a transmittance of less than 3.5% at 370nm and an average transmittance of more than 84.5% between 400nm and 800nm.

[0013] Furthermore, the 370nm UV cutoff cover glass for perovskite solar cell encapsulation has an average transmittance of less than 1.2% in the 300nm~380nm range.

[0014] A method for preparing a 370nm ultraviolet cutoff cover glass for perovskite solar cell encapsulation, characterized by comprising the following steps: (1) Weigh each component in the glass matrix and the UV cutoff functional agent as a mass percentage based on oxides; (2) All raw materials are dried before batching (drying at 90~120℃ for 2~5h) to remove adsorbed water on the surface of the raw materials and reduce the moisture content of the batch. By controlling the moisture content of the raw materials, the batching accuracy and mixing uniformity can be improved, and the bubbles, streaks and local component fluctuations caused by moisture evaporation during the melting process can be reduced, which is conducive to improving the optical uniformity and visible light transmittance stability of the glass. (3) After drying, the raw materials of each component are screened and pretreated, and then accurately mixed. The mixture is placed in a platinum-rhodium alloy crucible, melted and cast in a high-temperature furnace, and then annealed and cooled to obtain a low-stress 380nm ultraviolet cutoff cover glass for perovskite solar cell encapsulation.

[0015] Furthermore, the melting stage temperature is 1450℃~1700℃, and the constant temperature melting is maintained for 3~7 hours to ensure uniform melting and dispersion of functional components.

[0016] Furthermore, the annealing temperature after molding is 480℃~620℃, held for 2~5 hours, and the cooling rate is no higher than 1℃ / min, with gradient cooling to room temperature.

[0017] Furthermore, the thickness of the 370nm ultraviolet cutoff cover glass for encapsulating perovskite solar cells is 0.05mm to 6mm.

[0018] Furthermore, the 370nm UV cutoff cover glass for perovskite solar cell encapsulation is subsequently subjected to chemical or physical tempering treatment.

[0019] In this invention, CeO2, a UV cutoff functional agent, exhibits excellent UV absorption in glass, particularly showing significant inhibition in the 300–360 nm wavelength range. With increasing CeO2 content, the UV cutoff edge of the glass gradually shifts towards longer wavelengths, enhancing its UV shielding capability. TiO2 is a crucial component in this invention for adjusting the cutoff wavelength and enhancing the steepness of the cutoff edge. TiO2 itself possesses strong near-UV absorption characteristics; when incorporated into glass, it works synergistically with CeO2 to enhance absorption in the near-UV region and improve the transition morphology of the UV cutoff curve. The inventors' experiments revealed that using only CeO2 limits the range of cutoff edge control, and some formulations exhibit a relatively slow cutoff edge transition; using only TiO2 makes it difficult to achieve the target cutoff wavelength while maintaining high visible light transmittance. Combining CeO2 with TiO2 significantly improves the UV cutoff effect and makes the cutoff wavelength easier to control precisely. The addition of ZnO further enhances the UV cutoff effect. 2+ Once integrated into the glass network, the local oxygen coordination structure and electronic environment can be modulated, making it easier for cerium ions to maintain a high valence state distribution that is favorable for UV cutoff, and in particular, it helps to suppress Ce. 4+ To Ce 3+ The excessive conversion of Fe2O3 improves the stability and repeatability of UV cutoff performance. Fe2O3 is the auxiliary UV cutoff and cutoff edge redshift adjustment component in this invention. Fe2O3 mainly exists in glass as Fe... 3+ and a small amount of Fe 2+ It exists in form. Among them, Fe... 3+ It exhibits strong absorption in the ultraviolet and near-ultraviolet regions, particularly enhancing absorption around 350–400 nm, shifting the ultraviolet cutoff edge towards longer wavelengths. However, excessive addition may adversely affect visible light transmittance and glass chromaticity. V₂O₅ is introduced as an auxiliary ultraviolet cutoff component and a cutoff edge modulator. The V₂O₅ contains V₂O₅... 5+ It can form VO coordination structures with oxygen in the glass network, resulting in charge transfer absorption from oxygen to vanadium centers, thereby enhancing the glass's absorption capacity in the near-ultraviolet region. However, excessive addition may adversely affect visible light transmittance and glass color. Sm₂O₃ can serve as a rare-earth auxiliary spectral modulator. 3+ It possesses the characteristic electronic energy level structure of rare earth ions. When added in appropriate amounts, it can fine-tune the absorption in the near-ultraviolet and short-wave visible regions and help improve the spectral stability of glass under ultraviolet irradiation. However, when the amount added is too high, it may have an adverse effect on visible light transmittance and glass color.

[0020] Compared with the prior art, the present invention has the following advantages: By directly adding a UV-blocking functional agent to a glass substrate (sodium-calcium silicate glass, borosilicate glass, or aluminosilicate glass), a cover glass with UV blocking function can be directly prepared (transmittance less than 3.5% at 370nm, average transmittance greater than 84.5% from 400nm to 800nm, and average transmittance less than 1.2% from 300nm to 380nm), exhibiting excellent shielding effect and excellent visible light transmittance; furthermore, the cover glass prepared by this invention can be further strengthened (chemical or physical tempering); suitable for use as a cover glass for perovskite solar cells. Attached Figure Description

[0021] Figure 1 Transmittance diagram of soda-lime-silicon glass from 400nm to 800nm; Figure 2 Transmittance diagram of borosilicate glass from 400nm to 800nm; Figure 3 Transmittance of aluminosilicate glass from 400nm to 800nm. Detailed Implementation

[0022] The technical solution of the present invention is further described below through specific embodiments, but these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0023] A method for preparing a 380nm ultraviolet cutoff cover glass for perovskite solar cell encapsulation, the specific implementation steps of which are as follows: (1) First, put all raw materials into a 120℃ oven and dry them for 2 hours to remove the adsorbed moisture and avoid the introduction of moisture that could cause defects such as bubbles and streaks in the glass melting process. (2) Weigh each raw material according to the weight percentage listed in Table 1, pass it through a 200-mesh sieve to remove large agglomerated particles and ensure uniform particle size of the raw materials. (3) Mix the weighed raw materials evenly to form a mixture, and pour the mixture into a platinum-rhodium alloy crucible; place the platinum-rhodium alloy crucible containing the mixture into a high-temperature furnace and melt it at 1600℃ for 5 hours; after the melting stage is completed, pour the glass liquid into a mold, place the molded glass block into a muffle furnace, keep it at 550℃ for 3 hours, and then cool it to room temperature at a rate of 0.5℃ / min to obtain ultraviolet cut-off glass.

[0024] The obtained glass preform was cut, ground and polished to obtain a flat glass sample with a thickness of 4 mm. The optical transmittance of each sample was tested, and the specific test results are shown below.

[0025]

[0026] This invention's 370nm UV-cutoff glass significantly reduces the doping amount of UV-modifying components, substantially lowering raw material and manufacturing costs. It also eliminates performance redundancy issues, making it suitable for low-cost industrial mass production. Simultaneously, this invention effectively avoids the visible light absorption loss problem caused by high doping components, exhibiting superior visible light transmittance and maximizing the photoelectric conversion efficiency of perovskite solar cells, thus balancing excellent UV protection and high power generation performance.

[0027] The 370nm UV-cutoff glass prepared by this invention is applicable to three systems: soda-lime-silicon glass, borosilicate glass, and aluminosilicate glass. As shown in Table 1, the three glass systems exhibit significant performance differences: soda-lime-silicon glass has the best near-UV cutoff performance, but its visible light transmittance is relatively low; borosilicate glass and aluminosilicate glass have slightly weaker UV cutoff performance than soda-lime-silicon glass, but their visible light transmittance is superior. They can be flexibly selected according to different perovskite solar cell application scenarios and performance requirements.

[0028] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any person skilled in the art can make various changes, modifications, or equivalent substitutions to the technical solutions of the present invention using the disclosed methods and techniques without departing from the scope of the present invention, thus forming equivalent embodiments. Therefore, any simple modifications, equivalent substitutions, equivalent changes, and modifications made to the above embodiments without departing from the essence of the present invention are all within the protection scope of the present invention.

Claims

1. A 370nm UV cutoff cover glass for encapsulating perovskite solar cells, comprising a sodium-calcium silicate glass, borosilicate glass, or aluminosilicate glass substrate, characterized in that: UV blocking functional agents are added to the glass matrix. The UV blocking functional agents, expressed as a mass percentage based on oxides, have the following proportions in the glass matrix: CeO2: 1%~3%, TiO2: 1%~3%, Fe2O3: 0~2%, ZnO: 0.1%~1%, V2O5: 0~1%, Sm2O3: 0~1%.

2. The 370nm UV cutoff cover glass for perovskite solar cell encapsulation according to claim 1, characterized in that: The UV-blocking functional agent, expressed as a mass percentage based on oxides, has the following proportions in the glass matrix: CeO2: 1.2%-2.0%, TiO2: 1.2%-2.0%, Fe2O3: 0-1.0%, ZnO: 0.2%-0.5%, V2O5: 0-0.5%, Sm2O3: 0-0.5%.

3. The 370nm UV cutoff cover glass for perovskite solar cell encapsulation according to claim 1, characterized in that: The sodium-calcium silicate glass, expressed as a mass percentage based on oxides, is composed of the following substances: SiO2: 65-75%, Na2O: 10-25%, CaO: 5-15%, MgO: 1-5%, Al2O3: 0-3%.

4. The 370nm UV cutoff cover glass for perovskite solar cell encapsulation according to claim 1, characterized in that: The borosilicate glass, expressed as a mass percentage based on oxides, is composed of the following substances: SiO2: 75~83%, Na2O: 1~5%, B2O3: 6~15%, CaO: 0.5~2%, Al2O3: 0~3%.

5. The 370nm UV cutoff cover glass for perovskite solar cell encapsulation according to claim 1, characterized in that: The aluminosilicate glass, expressed as a mass percentage based on oxides, is composed of the following substances: SiO2: 60~69%, Na2O: 5~9%, Li2O: 2~5%, K2O: 1~5%, MgO: 3~9%, Al2O3: 16~24%.

6. A 370nm UV cutoff cover glass for encapsulating perovskite solar cells according to any one of claims 1 to 5, characterized in that: The aforementioned 370nm UV cutoff cover glass for perovskite solar cell encapsulation has a transmittance of less than 3.5% at 370nm and an average transmittance of greater than 84.5% from 400nm to 800nm.

7. A 370nm UV cutoff cover glass for encapsulating perovskite solar cells according to any one of claims 1 to 5, characterized in that: The 370nm UV cutoff cover glass used for encapsulating perovskite solar cells has an average transmittance of less than 1.2% in the 300nm~380nm range.

8. A method for preparing a 370nm ultraviolet cutoff cover glass for encapsulating perovskite solar cells according to any one of claims 1 to 5, characterized in that: (1) Weigh each component in the glass matrix and the UV cutoff functional agent as a mass percentage based on oxides; (2) Dry all raw materials before mixing; (3) After drying, the raw materials of each component are screened and pretreated, and then accurately mixed. The mixture is placed in a platinum-rhodium alloy crucible, melted and cast in a high-temperature furnace, and then annealed and cooled to obtain a low-stress 380nm ultraviolet cutoff cover glass for perovskite solar cell encapsulation.

9. The method for preparing a 370nm ultraviolet cutoff cover glass for perovskite solar cell encapsulation according to claim 8, characterized in that: The melting stage temperature is 1450℃~1700℃, and the melting is carried out at a constant temperature for 3~7 hours; the annealing temperature after molding is 480℃~620℃, and the temperature is held for 2~5 hours. The cooling rate is not higher than 1℃ / min, and the temperature is gradually cooled to room temperature.

10. The method for preparing a 370nm ultraviolet cutoff cover glass for perovskite solar cell encapsulation according to claim 8, characterized in that: The thickness of the 370nm UV cutoff cover glass for perovskite solar cell encapsulation is 0.05mm~6mm; further processing involves chemical or physical tempering.